Italian Historical Rural Landscapes Cultural Values for the Environment and Rural Development - Agnoletti, Mauro (Environmental History, 2013)
Over the last few decades, sustainable development and rural development policies have pursued strategies where farming has often been regarded as a factor disturbing or deteriorating the ecosystem. But the current economic, social and environmental problems of the Earth probably call for a different perspective. We should look for examples of a positive integration between human society and nature, study them, and apply the lesson learnt. This research work-a preliminary study conducted in view of the compilation of a national register of historical rural landscapes and traditional practices-presents more than a hundred case studies where the historical relationships between man and nature have generated, not deterioration, but cultural, environmental, social and economic values. The project has seen the participation of 14 universities and more than 80 researchers over 3 years. The results show that it is not only the economic face of globalization that is negatively affecting the landscape, but also inappropriate environmental policies denying the importance of cultural values. Now, however, something is beginning to change at the political and operational level. The recent CBD-UNESCO joint program on biocultural diversity acknowledges the importance of cultural values in landscape preservation, as do the FAO Globally Important Agricultural Heritage Systems project and several projects promoted by the International Union of Forest Research Organizations. In Europe, rural policies are showing a growing interest in the preservation of biodiversity and the landscape structure of a continent deeply shaped by its history and culture. The European Landscape Convention is inviting EU member states to develop specific policies in this regard, and Italy has included landscape as a strategic objective in its national plan for rural development. This research intends to support these new perspectives.